A cross-sectional study of prevalence and predictors of risky sexual behavior among school-going adolescents in Mbarara municipality, Uganda - Anyanwu, Michael U; Tamwesigire, Imelda (African Health Sciences, 2023)
Background: Adolescents in Sub-Saharan Africa are at a greater risk of experiencing the adverse consequences of risky sexual behavior such as unwanted pregnancy and school drop-out than adolescents from other regions. Objectives: This study determined the prevalence and identified the demographic, school and social factors associated with risky sexual behavior among secondary school students in Uganda. Methods: This was a quantitative cross-sectional study conducted in 12 secondary schools in Mbarara Municipality, Uganda. A self-reported questionnaire was used to estimate the prevalence and predictors of risky sexual behavior among the students. Results: Out of the 910 students, 314 (34.6%) were sexually active and almost two in every ten adolescents had engaged in risky sexual behavior 171 (18.8%). About 27 (8.7%) had been pregnant or impregnated their sexual partner while 143 (45.6%) used condoms consistently. Risky sexual behavior was associated with age, gender of the student as well as alcohol consumption, smoking and substance use. Conclusion: Most of the participants were not sexually active, however, among the sexually active students, more than half engaged in risky sexual behavior. This finding suggests the need to introduce comprehensive sex education with a focus on safe sex practices in secondary schools in Uganda.
Keywords: Prevalence; Risk factors; Sexual behavior